Strategies for Managing the Dual Risk of Sexually Transmitted Infections and Unintended Pregnancy Among Puerto Rican and African American Young Adults - Carter, Marion W. (American Public Health Association, 2012)
Although young adults in the United States are at increased risk for sexually transmitted infections (STIs) and unintended pregnancy, they do not report high rates of dual-method use (condoms plus other contraception) for prevention. We used prospective qualitative data from 69 urban Puerto Rican and African American individuals aged 18 to 25 years to determine how they managed these risks in their heterosexual relationships during a 4- to 8-week period. Hormonal or long-acting contraceptive use, condoms, and withdrawal were the most common unintended pregnancy prevention strategies; condoms, STI testing, and perceived fidelity were dominant among STI prevention strategies. We need to shift the focus from dual-method use toward a broader concept of dual protection to be more responsive to young adults’ concerns, perceptions, and priorities.